SEDENTARY BEHAVIOUR PADA ANAK USIA SEKOLAH DI KECAMATAN DENPASAR TIMUR - Luh Mira Puspita; Kadek Cahya Utami (Coping: Community of Publishing in Nursing, 2020)
Obese children are at high risk of becoming obese as adults and have the potential to experience diseases such as cardiovascular disease. Obesity will cause health problems in school-age children, which is around 20-30% of children suffer from hypertension, type 2 diabetes meillitus and sleep apnea. Children will also experience psychosocial disorders such as depression and low self-esteem. One of the causes of obesity in school-age children is sedentary behavior consisting of reading, sitting, and screen-based activity (watching television, playing video games, playing computers and playing smartphones). The results of research in Bali, especially in the city of Denpasar, children above ten years who do the most sedentary behavior is for 6 hours per day and the result is 44.0%. This study aimed to identify sedentary behavior in school age children. This type of research is deskriptive research and used a cohort study. Sample in this study were 122 elementary school children aged 10-12 years. The results obtained that the most sedentary behavior is often carried out by school-age children is screen-based activity especially watching television. Parents are advised to limit the activity of watching television to children and increasing physical activity.